Restore, Reform Or Transform Forestry Education In Uganda? - Buyinza, Mukadasi (Makerere Journal of Higher Education, 2009)
The role of participatory approaches to forestry has increased dramatically, and meeting the needs of people is now seen as a primary function of forestry. These changes present both strategic and practical challenges, constraints and opportunities for forestry education. The important changes in forestry education include the shift from teacher-to student-centred learning and rapid technological developments. If forestry education is to meet its new challenges, it needs to undergo deep transformation. This paper discusses the changing social perceptions and demands onto the forest sector and their implications to forestry education. It reflect on the current status of forestry education, and describes the drivers for change in the delivery of forest education in Uganda.
Keywords: Attitude goal, forestry education, forest sector, curricula, Uganda